Pathways of regional transformation and Industry 4.0. Issue 10 (2nd November 2021) - De Propris, Lisa; Bailey, David
ABSTRACT: We explore the impact of technological changes brought in by the Fourth Industrial Revolution on local systems of industrial specialization. To do so we connect the Evolutional Economic Geography literature on regional diversification with the literature on systems change, notably the multilevel perspective (MLP) framework, expanding the latter with a place-based dimension enabling the application of technological transition to regional economies. Here, a local system's ability to transform rests on three capabilities: innovation capabilities, docking capabilities and translational capabilities. Building on these, we identify four transformative paths: an endogenous transformative path; a hyper-transformative path; an importation transformative path; and a regional obsolescence path. We stress that local systems are not locked into a particular pathway, with implications for place-based industrial policy.